Strategies for Engineering Reproductive Sterility in Plantation Forests - Fritsche, Steffi; Klocko, Amy L.; Boron, Agnieszka; Brunner, Amy M.; Thorlby, Glenn (Frontiers in Plant Science, 2018)
A considerable body of research exists concerning the development of technologies to engineer sterility in forest trees. The primary driver for this work has been to mitigate concerns arising from gene flow from commercial plantings of genetically engineered (GE) trees to non-GE plantations, or to wild or feral relatives. More recently, there has been interest in the use of sterility technologies as a means to mitigate the global environmental and socio-economic damage caused by the escape of non-native invasive tree species from planted forests. The current sophisticated understanding of the molecular processes underpinning sexual reproduction in angiosperms has facilitated the successful demonstration of a number of control strategies in hardwood tree species, particularly in the model hardwood tree Poplar. Despite gymnosperm softwood trees, such as pines, making up the majority of the global planted forest estate, only pollen sterility, via cell ablation, has been demonstrated in softwoods. Progress has been limited by the lack of an endogenous model system, long timescales required for testing, and key differences between softwood reproductive pathways and those of well characterized angiosperm model systems. The availability of comprehensive genome and transcriptome resources has allowed unprecedented insights into the reproductive processes of both hardwood and softwood tree species. This increased fundamental knowledge together with the implementation of new breeding technologies, such as gene editing, which potentially face a less oppressive regulatory regime, is making the implementation of engineered sterility into commercial forestry a realistic possibility.